Aplikasi Solid Decanter dan EM4 terhadap Pertumbuhan dan Produksi Tanaman Melon (Cucumis melo L.) pada Tanah Alluvial - Iwandikasyah Putra; Muhammad Jalil; Jekki Irawan; Muhammad Afrillah; Chairudin Chairudin; Habibul Alamsyah Simamora; Iwan Saputra (Jurnal Agrotek Lestari, 2023)
The study aimed to look at the effect of solid decanter and EM4 applications on the growth and production of melon plants (Cucumis melo L.) on Alluvial. Solid decanter is a raw organic matter and requires decomposition with EM4 so that nutrients can be utilized properly by melon plants. This research was carried out December-April 2022 at the experimental garden of the Faculty of Agriculture, Teuku Umar University, West Aceh Regency, Aceh Province.  This study used a Randomized Group Design (RAK) factorial pattern of 4 x 4 with 3 repeats. The first factor is Solid Decanter (S) which consists of S0 (control), S1 (90 gr), S2(180 gr), S3(270 gr) and the second factor is EM4 (E) which consists of E0 (control), E1 (10ml), E2 (20ml), E3 (30ml). The results showed an interaction between solid decanter and EM4 against the diameter of the stem of melon plants at 14 HST.  This best treatment was found in the combination of S2E1 treatment, where the solid decanter dose of S2(180 gr) and EM4 E1 (10 ml) differed markedly from other treatment combinations.